Las pinturas murales de la iglesia de San Pedro de Torremocha de Jarama - González Hernando, Irene; Manzarbeitia Valle, Santiago; Azcárate Luxán, Matilde; Monge Zapata, Aitana (Anales de Historia del Arte, 2010)
Sin resumen